Short Term CO2 Enrichment Increases Carbon Sequestration of Air-Exposed Intertidal Communities of a Coastal Lagoon - Mishra, Amrit K.; Silva, João; Santos, Rui (Frontiers in Marine Science, 2018)
In-situ production responses of air-exposed intertidal communities under CO2 enrichment are reported here for the first time. We assessed the short-term effects of CO2 on the light responses of the net community production (NCP) and community respiration (CR) of intertidal Z. noltei and unvegetated sediment communities of Ria Formosa lagoon, when exposed to air. NCP and CR were measured in-situ in summer and winter, under present and CO2 enriched conditions using benthic chambers. Within chamber CO2 evolution measurements were carried out by a series of short-term incubations (30 min) using an infra-red gas analyser. Liner regression models fitted to the NCP-irradiance responses were used to estimate the seasonal budgets of air-exposed, intertidal production as determined by the daily and seasonal variation of incident photosynthetic active radiation. High CO2 resulted in higher CO2 sequestration by both communities in both summer and winter seasons. Lower respiration rates of both communities under high CO2 further contributed to a potential negative climate feedback, except in winter when the CR of sediment community was higher. The light compensation points (light intensity where production equals respiration) of Z. noltei and sediment communities also decreased under CO2 enriched conditions in both seasons. The seasonal community production of Z. noltei was 115.54 ± 7.58 g C m-2 season-1 in summer and 29.45 ± 4.04 g C m-2 season-1 in winter and of unvegetated sediment was 91.28± 6.32 g C m-2 season-1 in summer and 25.83± 4.01 g C m-2 season-1 in winter under CO2 enriched conditions. Future CO2 conditions may increase air-exposed seagrass production by about 1.5-fold and unvegetated sediments by about 1.2 fold.I